2022
DOI: 10.2147/dddt.s358092
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Anlotinib with or without PD-1 Blockades in the Treatment of Patients with Advanced Primary Hepatocellular Carcinoma: A Retrospective, Real-World Study in China

Abstract: Purpose Anlotinib, a novel multi-target tyrosine kinase inhibitor, has shown encouraging antitumor effects in advanced hepatocellular carcinoma (HCC). This study evaluated the effectiveness and safety of anlotinib with or without programmed death-1 (PD-1) blockades for patients with advanced primary HCC in a real-world setting in China. Patients and Methods Between July 2019 and May 2021, 27 patients with advanced primary HCC who received at least 2 cycles of anlotinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…When HCC is expected to become a new approved indication for anlotinib, taking into account the possible future drug resistance in advance, combination therapy is an effective way to improve the e cacy of anlotinib in the future. As mentioned earlier, the combination of anlotinib with immunotherapy has also been shown to be safe in clinical trials and provides promising clinical bene ts in patients with unresectable or metastatic HCC who have not received systemic therapy 7,11 . As an anti-angiogenic drug, anlotinib inhibits tumor angiogenesis to achieve the purpose of anti-tumor.…”
Section: Discussionmentioning
confidence: 95%
“…When HCC is expected to become a new approved indication for anlotinib, taking into account the possible future drug resistance in advance, combination therapy is an effective way to improve the e cacy of anlotinib in the future. As mentioned earlier, the combination of anlotinib with immunotherapy has also been shown to be safe in clinical trials and provides promising clinical bene ts in patients with unresectable or metastatic HCC who have not received systemic therapy 7,11 . As an anti-angiogenic drug, anlotinib inhibits tumor angiogenesis to achieve the purpose of anti-tumor.…”
Section: Discussionmentioning
confidence: 95%
“…In patients with advanced non-small-cell lung cancer, many clinical studies demonstrated that anti-PD-1 treatment concomitant with anlotinib has favorable antitumor activities as the first-line or posteriorline therapeutic options [10][11][12][13]. In patients with advanced HCC, anlotinib alone could yield a promising efficacy irrespective of whether patients received PD-1 blockades [14]. Two clinical trials reported that when combined with PD-1 blockades, anlotinib showed more robust antitumor activities with an objective response rate of over 30% as the first-line treatment of advanced HCC [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…( 5) There was no hypertension. (6) The patient signed the informed consent form. The main exclusion criteria were as follows:…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Studies have shown that anlotinib (ANL) is effective and well tolerated as a treatment for patients with advanced HCC. 5,6 The results showed that fluorouracil was effective for HCC. [7][8][9] Both S1 and capecitabine are fluorouracils.…”
Section: Introductionmentioning
confidence: 99%